Kladivasti prst - Fortuna, Krištof (Medicinski razgledi, 2024)
A mallet finger is a deformity of the fingertip in which the distal interphalangeal joint is flexed, and full active extension of the distal phalanx is not possible. It typically results from a traumatic disruption of the terminal extensor tendon at its insertion at the proximal part of the distal phalanx or slightly proximally at the level of the distal interphalangeal joint. There are two types: soft tissue mallet finger and bony mallet finger. The bony type results from an avulsion of the tendon from the distal phalanx along with a small bony fragment attached to the avulsed tendon. Depending on the condition of the overlying skin, a mallet finger is classified as open or closed. The most common mechanism of mallet finger injury is forced flexion at the distal interphalangeal joint during active contraction of the finger’s extensor tendon. Patients typically describe pain at the affected joint, accompanied by deformity and functional impairment. To precisely define the type of injury, X-ray imaging of the injured finger in two projections is performed. Most mallet fingers are treated conservatively with splints, with the distal interphalangeal joint in extension. Surgical treatment is usually indicated for mallet fingers involving more than one-third of the joint surface and in patients with a volar subluxation of the distal phalanx. Research has not conclusively demonstrated significant advantages of surgical treatment over conservative; the key is to tailor treatment to each patient individually. Failure to recognize and treat a mallet finger can lead to chronic deformities that further impair finger and hand function.
Keywords: avulzija tetive; distalna falanga; distalni interfalangealni sklep; kostni kladivasti prst; mehkotkivni kladivasti prst; opornica; tetiva iztezalka prsta